Blended Education In The Process Of Modern Education - Zarifa Mukaddamovna Kabirova (Euro Asian Journal Publishing, 2024)
The article analyzes the potential and possibilities of the mixed education method as a didactic tool for making the transition from the traditional educational model to integrated education, involving the electronic environment and resources. Existing models of mixed education are reviewed, methods of adapting them to the conditions of the Russian university system are discussed. The problems that hinder the effective and rapid integration of elearning environments are identified and some strategic initiatives are proposed to solve them
Keywords: mixed education; information technology; electronic education